2007
DOI: 10.1093/ps/86.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet and Stress Mimicked by Corticosterone Administration on Early Postmortem Muscle Metabolism of Broiler Chickens

Abstract: Three experiments were conducted to evaluate the effects of preslaughter physiological states mimicked by long- or short-term administration of corticosterone (CORT) and dietary energy sources on muscle glycogen contents and meat quality of broiler chickens. In experiment 1, the broilers were fed a high lipid diet (LD) or a normal diet (ND) that differed in carbohydrate (3.8%) and lipid (2.5%) contents from 21 d of age. From 28 d of age onwards, 50% of the chickens in each dietary treatment were subjected to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…• Increasing circulating concentrations of glucose (Lin et al, 2007;Jiang et al, 2008;Yuan et al, 2008;Zhao et al, 2009) although depressed circulating concentrations of glucose have also been reported (Gao et al, 2008) • Increasing circulating concentrations of insulin (Jiang et al, 2008;Yuan et al, 2008;Zhao et al, 2009 • Increased breast muscle glycogen (Lin et al, 2007) but lower levels have also been reported (Gao et al, 2008). Despite the marked effects on glucose metabolism, circulating concentrations of lactate are unchanged in chickens receiving glucocorticoid administration (Lin et al, 2007).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
See 4 more Smart Citations
“…• Increasing circulating concentrations of glucose (Lin et al, 2007;Jiang et al, 2008;Yuan et al, 2008;Zhao et al, 2009) although depressed circulating concentrations of glucose have also been reported (Gao et al, 2008) • Increasing circulating concentrations of insulin (Jiang et al, 2008;Yuan et al, 2008;Zhao et al, 2009 • Increased breast muscle glycogen (Lin et al, 2007) but lower levels have also been reported (Gao et al, 2008). Despite the marked effects on glucose metabolism, circulating concentrations of lactate are unchanged in chickens receiving glucocorticoid administration (Lin et al, 2007).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Despite the marked effects on glucose metabolism, circulating concentrations of lactate are unchanged in chickens receiving glucocorticoid administration (Lin et al, 2007). There is a growing viewpoint that corticosterone acts via induction of insulin resistance.…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
See 3 more Smart Citations